2012
DOI: 10.2519/jospt.2012.3798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neurocognitive and Balance Deficits in Collegiate Football Players Without Clinically Diagnosed Concussion

Abstract: Study Design Prospective cohort. Objectives To identify the prevalence of neurocognitive and balance deficits in collegiate football players 48 hours following competition. Background Neurocognitive testing, balance assessments, and subjective report of symptoms are a test battery commonly used to examine athletes suspected of having sustained a concussion. Previous literature suggests that many concussions go unreported. Little research exists examining the prevalence of neurocognitive or balance deficits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
(40 reference statements)
0
26
0
Order By: Relevance
“…It is generally agreed that a comprehensive battery of neurological function and clinical balance tests needs to be administered to assess, diagnose and predict the prognosis of a concussed athlete [27]. One of the many ways to assess an athlete's return to play following a concussion is to assess their mechanical impairments, which includes motor control and postural stability issues [24,28,29]. The measures collected in our study can be used in addition to and in support of the recommended battery of tests already used for concussion management (i.e., the reaction time test, the cognition test, balance assessments) [28], especially in establishing baseline measures.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that a comprehensive battery of neurological function and clinical balance tests needs to be administered to assess, diagnose and predict the prognosis of a concussed athlete [27]. One of the many ways to assess an athlete's return to play following a concussion is to assess their mechanical impairments, which includes motor control and postural stability issues [24,28,29]. The measures collected in our study can be used in addition to and in support of the recommended battery of tests already used for concussion management (i.e., the reaction time test, the cognition test, balance assessments) [28], especially in establishing baseline measures.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 643) As a result, the symptoms of a concussion may not emerge until several minutes or even hours after the concussive incident (Marar, McIlvain, Fields, & Comstock, 2012). Although the athlete may feel dazed or "out-of-it," increased adrenaline from the pressure of game-time situations, such as described by Kramer, Pereira and Mascherano may not allow an athlete to relate to an evolving concussive injury to a specific hit or collision (Mulligan, Boland, & Payette, 2012). In addition, because concussions may cloud short-term memory, athletes who become concussed may not recall the level of an impact when symptoms ultimately emerge (Harmon et al, 2013).…”
Section: Assumption Of Riskmentioning
confidence: 99%
“…In addition, because concussions may cloud short-term memory, athletes who become concussed may not recall the level of an impact when symptoms ultimately emerge (Harmon et al, 2013). Thus, the athlete may not seek care from health professionals if they are unable to recognize or associate their symptoms with concussive event (Mulligan et al, 2012).…”
Section: Assumption Of Riskmentioning
confidence: 99%
“…7 A second study comparing athletes (none with a diagnosed concussion) in contact sports (hockey and football) with athletes in noncontact sports found that at postseason testing, a higher proportion of athletes in contact sports had impairments on select memory tests. 8 A small sample of high school football players (4 of 11) demonstrated significant impairments on tests of neurophysiological and neurocognitive functioning within 72 hours after game participation. 9 Finally, 1 other study demonstrated no difference on a screening assessment of cognitive and balance functioning at 3 time intervals during the season.…”
Section: Introductionmentioning
confidence: 99%